Pollution Bactérienne Et Toxique Dans Les Eaux Des Rejets Industriels Et Domestiques Du Littoral Atlantique (Casablanca Est- Maroc) - Siba, Amine; Eljaafari, Samir; Mokhtari, Faouzia (European Scientific Journal, ESJ, 2018)
In this work, we will focus on the assessment of the quality of the Casablanca EST coastline, including bacterial and toxic water pollution, before the realization of the SIDI BERNOUSSI pre-treatment station. For this purpose, a set of analyzes were carried out on the littoral waters to evaluate the quality of sea water. This companion of analyzes includes: Analyzes on the surface of the sea water: Physico-chemical parameters: pH, temperature, biological oxygen demand BOD 5. Undesirables substances: Nitrates (NO3-), Ammonium (NH4+), Phosphates (PO4-), Hydrocarbons. Bacteriological parameters: Faecal coliforms and faecal streptococci. Sediment Analysis: Arsenic (As), Barium (Ba), Cadmium (Cd), Total Chromium (CrT), Copper (Cu), Iron (Fe), Mercury (Hg), Lead (Pb), Selenium (Se), Zinc (Zn). Biodiversity analyzes: For algae: Arsenic (As), Cadmium (Cd), Mercury (Hg), Lead (Pb). For mussels: Cadmium (Cd), Mercury (Hg), Lead (Pb). The results showed that the waters of the east coast of Casablanca are contaminated with pollutants in this case pathogenic bacteria, toxic substances including heavy metals and other toxic substances; on the other hand, coastal biodiversity is also affected. This contamination is due to industrial activity in the area. but remains below, for most pollutants, normative limits. For bacteriological pollution, beaches AIN SEBAA and NAHLA recorded a coliform contamination and faecal streptococci exceeding the values of the Moroccan norm of bathing water.